Fearless - Michaels, Fern (New York : Kensington Publishing Corp., 2020)
Anna Campbell is ready to take her first tentative steps back into the world after widowhood. On a singles cruise, she meets divorced professor Ryan Robertson, and the sparks between them are undeniable. Back home in West Texas, Anna and Ryan continue their romance, and Anna decides it's time for their families to meet. Anna is delighted when her daughter, Christina, hits it off with Ryan's daughter, Reneé. The two girls are close in age and have lots in common. Ryan's son, Patrick, is college-bound and somewhat aloof, but Anna feels sure they'll grow closer in time. She happily accepts Ryan's proposal, confident in the bond they've formed. -- provided by publisher.
Includes recipe.
Keywords: Widows -- Fiction; Man-woman relationships -- Fiction; Families -- Fiction; Texas -- Fiction; Romance fiction; Thrillers (Fiction)